Radial waveguide slot array antenna design and implementation for WLAN applications - Abdul Razak, Lway Faisal (Penerbit UTM, 2008)
The recent growth in the information techno logy and wireless communications has created m any opportunities for enhancing the performance of existing signal transmission. However, Antenna designers are always searching for ways to improve existing designs or introduce novel designs in order to achieve desirable radiation characteristics, reduce the size and weight, which are mandatory requirement for antennas used in W LAN and thus make antennas m ore cost efficient. Transmission of data at higher rates requires adequate bandwidth for the elements characterize the communication link accordant to IEEE802.11b/g standard which well-hand led in this project.